Design of Biodiesel Application Engine with Jiangfa Engine - Wiliandi Saputro,; Akhmad Khairul Faizin,; Erwan Adi Saputro, (IPTEK The Journal for Technology and Science, 2026)
Currently, the public interest is still quite high for fossil fuels as indicated by the increase in fuel consumption which requires imports to meet domestic fuel needs. the negative impact of the use of fossil fuels is the availability of crude oil that continues to decline and the problem of exhaust emissions is increasingly concerning. the use of fossil fuels must be reduced by substitution of alternative fuels, especially in diesel engines. One alternative fuel is biodiesel which can be used directly in diesel engines without having to modify engine components. Biodiesel is a fuel produced from the transesterification process. Biodiesel can be produced by utilizing vegetable oils, animal fats, used cooking oil, and algae so that biodiesel can be said to be a renewable, biodegradable, non-toxic, and environmentally friendly fuel because the exhaust emissions produced are relatively cleaner. In applications in everyday life diesel engines are often used to drive generators. In use in Indonesia, the government encourages to mix biodiesel with diesel oil. Now it has reached B30 biodiesel, which is 30% biodiesel and 70% diesel oil. Diesel motors or diesel engines are required to use B30 by the government. Therefore, this study aims to create a setup machine as a learning medium for biodiesel applications in diesel engines and to facilitate several types of research on diesel engines with biodiesel fuel, because the trainer form is simple but still has the same function. The method used in this research consists of 3 stages, namely design, manufacture, and performance testing using halogen lamps as an output. The results of this study is that this simple diesel engine design can work properly shown by halogen lamps which all 4 were lit during testing process.